Karakteristik fisikokimia dan fungsional tepung Sargassum polycystum sebagai bahan baku pembuatan garam fungsional: Physicochemical and functional characteristics of Sargassum polycystum flour as raw material for production of functional salt - Ramlan, Ramlan; Prangdimurti, Endang; Adawiyah, Dede Robiatul; Nurjanah, Nurjanah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Sargassum polycystum is highly abundant in Indonesian waters. S. polycystum still needs to be utilized optimally in the food and non-food sectors. This study aimed to determine the characteristics of S. polycystum flour from the waters of Cibuaya Beach, Ujung Genteng, and Sukabumi as a raw material for the production of functional salts. The study consisted of two main stages: the manufacture and characterization of S. polycystum flour. The parameters analyzed included yield, color, water activity, proximate content, minerals, NaCl, heavy metals, phytochemicals, total phenolics, flavonoids, phlorotannins, and antioxidant activity (DPPH and FRAP). The physical characteristics of S. polycystum flour include yield 79.52%, L* 44.36±0.33 (dark), a* 5.14±0.11 (red), b* 16.51±0.33 (yellow), and ºhue 72.61±0.01 (red-yellow). Chemical characteristics of S. polycstum flour include ash 34.43±0.19%, Na mineral 54.32±0.09 mg/g, K 87.12±0.48 mg/g, Na/K mineral ratio 0.62±0.00, and NaCl content 17.11±0.18%. Functional characteristics of S. polycystum flour include alkaloids, phenolics, saponins, and steroids (in qualitative testing); and contains total of phenolics 847.05±0.46 mg GAE/g sample, flavonoids 892.20±0.63 mg QE/g sample, phlorotannins 534.11±0.73 mg PGE/g sample; and antioxidant activity DPPH (IC50 value) 52.25±0.52 ppm (strong), and FRAP 242.93±2.31 µmmol FeSO4. S. polycystum flour has good physical, chemical, and functional characteristics, so it has the potential to be used as raw material for production of functional salt which is beneficial for body health.